Extracellular Vesicles and Autophagy in Osteoarthritis. (18th December 2016) - Gao, Tianyang; Guo, Weimin; Chen, Mingxue; Huang, Jingxiang; Yuan, Zhiguo; Zhang, Yu; Wang, Mingjie; Li, Penghao; Peng, Jiang; Wang, Aiyuan; Wang, Yu; Sui, Xiang; et al.
Abstract : Osteoarthritis (OA) is a type of chronic joint disease that is characterized by the degeneration and loss of articular cartilage and hyperplasia of the synovium and subchondral bone. There is reasonable knowledge about articular cartilage physiology, biochemistry, and chondrocyte metabolism. However, the etiology and pathogenesis of OA remain unclear and need urgent clarification to guide the early diagnosis and treatment of OA. Extracellular vesicles (EVs) are small membrane-linking particles that are released from cells. In recent decades, several special biological properties have been found in EV, especially in terms of cartilage. Autophagy plays a critical role in the regulation of cellular homeostasis. Likewise, more and more research has gradually focused on the effect of autophagy on chondrocyte proliferation and function in OA. The synthesis and release of EV are closely associated with autophagy. At the same time, both EV and autophagy play a role in OA development. Based on the mechanism of EV and autophagy in OA development, EV may be beneficial in the early diagnosis of OA; on the other hand, the combination of EV and autophagy-related regulatory drugs may provide insight into possible OA therapeutic strategies.